Preparing and characterizing biodegradable materials for ureteral stents. (20th July 2021) - Cui, Haipo; Zhang, Kui; Gao, Chenguang; Kang, Yahong; Jiang, Hongyan; He, Yingrong
Abstract: The development and application of biodegradable ureteral stents is of clinical significance for patients with ureteral stenosis and obstruction. We prepared five types of degradable monofilament, namely poly‐L‐lactide, poly(L‐lactide‐co‐ glycolide) (85% L‐lactide, 15% glycolide), poly(L‐lactide‐co‐glycolide‐co‐ε‐ caprolactone) (89% L‐lactide, 8% glycolide, and 3% ε‐caprolactone), poly(L‐lactide‐ co‐D, L‐lactide) (95% L‐lactide, 5% D, L‐lactide), and poly(lactide‐co‐ε‐caprolactone) (95% L‐lactide, 5% ε‐caprolactone), by melt extrusion and secondary drawing processes, after which degradation experiments were carried out in simulated urine at 37°C for 2 months. Because residues in the urinary systems of patients can cause complications, it is important that biodegradable ureteral stents are completely degraded after 6 weeks. Poly‐L‐lactide did not completely degrade under the abovementioned conditions and its molecular weight changed little. On the other hand, the poly(L‐lactide‐co‐glycolide) monofilament degraded slightly faster than that prepared from poly‐L‐lactide; however it maintained a certain mechanical strength after 8 weeks, which is not ideal for a woven ureteral stent. The poly(L‐lactide‐co‐D, L‐lactide), poly(L‐lactide‐co‐glycolide‐co‐ε‐caprolactone), and poly(lactide‐co‐ε‐caprolactone) monofilaments exhibited good tensile strengths and elongations at break in the first four weeks, which were reduced to almost zero in the eighth week. Ureteral stents made of these polymers can open narrow urethras at early stages and degrade completely at later stages. Based on its degradation rate, we conclude that the poly(lactide‐co‐ε‐caprolactone) monofilament is the best material for the preparation of ureteral stents.